1981
DOI: 10.1037/h0077845
|View full text |Cite
|
Sign up to set email alerts
|

Satiety role of the small intestine examined in sham-feeding rhesus monkeys.

Abstract: A sham-feeding preparation utilizing rhesus monkeys was employed to investigate the anatomical site of origin of satiety signals in the gastrointestinal tract. A series of experiments in which food was diverted from the stomach, the small intestine, or both demonstrated that (a) food acting at the pregastric level is not sufficient to produce normal-sized meals, (b) the accumulation of food in the small intestine is necessary to produce normal-sized meals, and (c) a potent preabsorptive or postabsorptive satie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Intestinal nutrient infusions reduce food intake in many species, including humans (14) - an effect that commences within seconds of nutrient infusion, indicating that at least some of the associated satiation signals emanate from the gut, rather than from postabsorptive sources (22). These, and other, findings demonstrate that the intestines play a dominant role in satiation.…”
Section: Intestinal Satiationmentioning
confidence: 78%
“…Intestinal nutrient infusions reduce food intake in many species, including humans (14) - an effect that commences within seconds of nutrient infusion, indicating that at least some of the associated satiation signals emanate from the gut, rather than from postabsorptive sources (22). These, and other, findings demonstrate that the intestines play a dominant role in satiation.…”
Section: Intestinal Satiationmentioning
confidence: 78%
“…5). It has been shown that free drinking behavior in water-deprived monkeys is controlled by many factors acting on different time scales, such as cellular dehydration, intestinal stimulation by water, gastric distension, and oropharyngeal metering (Gibbs et al 1981;Maddison et al 1980;Rolls and Rolls 1982;). The quality of the sigmoid function fit to our data shows that the collective effects of all these factors on the behavior can be described with a simple phenomenological model.…”
Section: Role Of the Internal Statementioning
confidence: 99%
“…Considerable advances have been made in understanding the mechanisms by which nutrients in the intestine suppress intake in a number of species (30,33), including rats (42,51,53) and humans (74). For example, it is well documented that intestinal carbohydrates reduce food intake in a dose-responsive manner (53,76) by preabsorptive (63,78) as well as postabsorptive (71) factors, largely through vagal afferent pathways (78,79).…”
mentioning
confidence: 99%